2022
DOI: 10.3390/cancers14194599
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Clinical Aspects of Metastatic Spinal Tumors

Abstract: Spine metastases are a common life-threatening complication of advanced-stage malignancies and often result in poor prognosis. Symptomatic spine metastases develop in the course of about 10% of malignant neoplasms. Therefore, it is essential for contemporary medicine to understand metastatic processes in order to find appropriate, targeted therapeutic options. Thanks to continuous research, there appears more and more detailed knowledge about cancer and metastasis, but these transformations are extremely compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 295 publications
0
4
0
Order By: Relevance
“…Their ability to differentiate in multiple directions and to secrete a variety of bioactive factors make them promising for a wide range of applications in autologous stem cell transplantation. In addition, the potential of ADMSCs in neural differentiation has been recognized ( Litak et al, 2022 ), and these ADMSCs-derived neural cells have been shown to promote neural repair. More importantly, ADMSCs exhibit low immunogenicity and tumorigenicity.…”
Section: Combined Application Of Biomaterialsmentioning
confidence: 99%
“…Their ability to differentiate in multiple directions and to secrete a variety of bioactive factors make them promising for a wide range of applications in autologous stem cell transplantation. In addition, the potential of ADMSCs in neural differentiation has been recognized ( Litak et al, 2022 ), and these ADMSCs-derived neural cells have been shown to promote neural repair. More importantly, ADMSCs exhibit low immunogenicity and tumorigenicity.…”
Section: Combined Application Of Biomaterialsmentioning
confidence: 99%
“…In the course of spine disorders, pain symptoms commonly occur [ 11 , 12 ]. According to available epidemiological studies, a neuropathic component of pain is often present in patients with spinal diseases, with a frequency ranging from 36% to 55% of patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of spine metastases is mostly palliative, and it is aimed at preserving or improving quality of life, as well as the protection or restoration of neurological functions and spinal stability [ 3 ]. Currently, bone-targeted agents are the mainstay of treatment of spine metastases, and their use can limit the incidence of SREs; however, their influence on survival is rather limited [ 5 ].…”
Section: Introductionmentioning
confidence: 99%